TINJAUAN HUKUM PELAKSANAAN HAK ANAK AKIBAT TERJADINYA PERKAWINAN DI BAWAH UMUR (STUDI KASUS PUTUSAN PENGADILAN AGAMA AMBARAWA Nomor 147/Pdt.P/2023/PA.Amb) - Yulian Christianto, Marselinus; Gultom, Potler (LEX LAGUENS: Jurnal Kajian Hukum dan Keadilan, 2024)
This study examines the legal review of the implementation of children's rights as a result of underage marriage, with a case study of the Decision of the Ambarawa Religious Court Number 147/Pdt.P/2023/PA.Amb. The main focus of this research is how children's rights are affected by early marriage and the legal considerations used by judges in deciding marriage dispensation cases. This research employs a normative juridical method with a legal and court decision approach. The findings indicate that underage marriage can impact the fulfillment of children's rights, particularly in terms of education, health, and overall well-being. Law Number 35 of 2014 on Child Protection and Law Number 16 of 2019 on Marriage establish a minimum marriage age to protect children. In the Ambarawa Religious Court case, the marriage dispensation request was denied because the female applicant was only 17 years old, and there were no urgent reasons to justify an exemption from the legal requirements. The judge considered that the marriage age restriction aims to protect children from the negative consequences of early marriage, such as mental and economic unpreparedness. Therefore, the court's decision reaffirmed that marriage dispensation can only be granted in highly urgent situations supported by sufficient evidence, which was not met in this case.